Digital Communication and Citizenship: The Action of Social Movements and Countermovements During the Covid-19 Pandemic - Luvizotto, Caroline Kraus [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Arquitetura Artes & Comun, 2022)
In Brazil, the Covid-19 pandemic promoted a narrative dispute between social movements and countermovements around the severity and ways of coping with the pandemic. Through a systematic literature review, this text presents a reflection on the performance of social movements in the face of the impacts of the pandemic and the mobilization caused by countermovements, emphasizing the importance of digital communication in the context. The crisis provoked by the Covid-19 pandemic must be treated as a moment of rupture that brought about significant changes in our lives and our societies. It is imperative to understand the dynamics established between social movements and countermovements during the Covid-19 pandemic so that citizen values are ensured during and after the crisis.
Keywords: Digital Communication; Social movements; Countermoves; Covid-19 pandemic